2022
DOI: 10.1007/jhep02(2022)119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of two-dimensional latticed holographic system

Abstract: We study the anisotropic properties of dynamical quantities: direct current (DC) conductivity, butterfly velocity, and charge diffusion. The anisotropy plays a crucial role in determining the phase structure of the two-lattice system. Even a small deviation from isotropy can lead to distinct phase structures, as well as the IR fixed points of our holographic systems. In particular, for anisotropic cases, the most important property is that the IR fixed point can be non-AdS2 × ℝ2 even for metallic phases. As th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…No similar features have been found in other holographic models with spatial anisotropy, see e.g. [46][47][48] 19 . Moreover, it was found that for a large class of black holes, the ratio of thermal conductivity to electric conductivity ¯s k = L T has an upper bound ¯r  L s 2 2 [49].…”
Section: Conclusion and Discussionsupporting
confidence: 62%
“…No similar features have been found in other holographic models with spatial anisotropy, see e.g. [46][47][48] 19 . Moreover, it was found that for a large class of black holes, the ratio of thermal conductivity to electric conductivity ¯s k = L T has an upper bound ¯r  L s 2 2 [49].…”
Section: Conclusion and Discussionsupporting
confidence: 62%
“…e express sorting system connects five parts: control equipment, conveying equipment, information collection equipment, classification equipment, and sorting crossing through communication technology. Sometimes, it must cooperate with manual assistance to form a complete express sorting system [10,11]. An automatic sorting system mainly has two characteristics: high sorting efficiency and low sorting error rate.…”
Section: Sorting System Based On Qr Code Information Recognitionmentioning
confidence: 99%
“…For example, the Rényi entropy has been proposed proportional to the JHEP08(2022)123 area of the minimum cosmic brane [22], which back-reacts on the background geometry. Meanwhile, the entanglement of purification, reflected entropy and the entanglement negativity have all been related to the minimum cross-section in the entanglement wedge (EWCS) [23][24][25][26][27][28][29][30][31][32]. In addition, quantum complexity has been proposed proportional to the volume or the action of a certain region, that can capture quantum information other than the entanglement [33].…”
Section: Introductionmentioning
confidence: 99%